Implementation of Mother's School to Prevent Stunting "Secanting" among Mothers in Bange Village, Sanggau Ledo District - Lidia Hastuti; Indri Erwhani; Ridha Mardiani; Zerry Erlando; Hapiz; Nur Ahlam Nadia Putri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Background: Mothers have a relatively low level of education, lack of knowledge and understanding about the importance of care during pregnancy to maintain the health of the mother and baby and nutritional needs during pregnancy and for the baby/child, failure to provide exclusive breastfeeding, early marriage, and early pregnancy due to unwanted pregnancies, pregnancies that are too close together, anemia in pregnant women are thought to be triggers for stunting. The Secanting program and health education for teenagers is an alternative action to help minimize the incidence of stunting. Objective: Increase knowledge, attitudes, and behavior of pregnant women and teenagers to prevent stunting by optimizing community empowerment for independence in health. Method: The mapping intervention approach in community-based implementation in program development is packaged in the form of maternal schools to prevent stunting abbreviated as "Secanting" and school-based sexual health education activities for teenagers in high school. Results: Before being given the Secanting program, pregnant women had an average knowledge score of 69.09±11.36, and after being given an average knowledge score of 86.36±8.09. There is a difference in the average score, amounting to 17.27 ± 13.48. The results of observations made regarding the skills of pregnant women in selecting, processing nutritious food ingredients, preparing menus, and serving, showed that before participating in the program, pregnant women had skills with an average score of 58.18 ± 7.5 and after being given the average score skills 81.81±7.5. There is a difference in the average score, amounting to 23.64 ± 8.08. There is an increase in knowledge and skills in pregnant women after being given the Secanting program. The program for adolescents shows that, before being given health education, adolescents know with an average score of 78.67 ± 4.24, and after being given an average knowledge score of 98.44 ± 11.40. There is a difference in the average score, amounting to 19.77 ± 10.33. There is an increase in knowledge in adolescents after being given health education. Conclusion: The Secanting program has proven effective in increasing knowledge in pregnant women and health education has proven effective in increasing knowledge in adolescents.